RECONSTRUCTION OF PEACE AGREEMENT IN INHERITANCE CASES (CASE STUDY OF THE ROLE OF MEDIATORS IN BONDOWOSO RELIGIOUS COURT) - Musfirohtul Hasanah; Alviatul Umroh; Hulliyatul Asfiya; Hoirotul Jaliyah; Siti Aisyah; Faiseh Dwi Cahyantari; Colilah; Selvin Nabila; Putri anisa; Lailatul Mkarromah; Qoidul Khoir (International Journal of Multidisciplinary Reseach, 2026)
Inheritance disputes are a common form of family dispute, particularly regarding the distribution of assets inherited by the testator. Differences of opinion among heirs often lead to conflict that has the potential to damage family relationships. Therefore, mediation is one dispute resolution method that can be used to reach a peaceful agreement. This study aims to determine the model for reconstructing a peaceful agreement in inheritance cases based on Islamic legal principles and religious court regulations, the role of the mediator in facilitating a peaceful agreement, and the supporting and inhibiting factors in achieving a peaceful agreement in inheritance cases at the Bondowoso Religious Court. This study used a qualitative research method with a case study approach. Data were obtained through interviews with the mediator and data collection from relevant sources. The results indicate that the ideal model for reconstructing a peaceful agreement in inheritance cases is achieved through a mediation approach that combines the principles of deliberation with an understanding of Islamic inheritance law, particularly through the science of faraid. In this process, the mediator acts as a facilitator, helping the parties understand the rights of each heir, establishing good communication, and encouraging the achievement of a mutual agreement. Furthermore, the success of mediation in inheritance cases is influenced by several factors, including the good faith of the parties, an understanding of Islamic inheritance law, and the mediator's ability to create a conducive mediation atmosphere. Conversely, frequently encountered inhibiting factors include long-standing family conflicts, a lack of understanding regarding inheritance distribution, and a lack of cooperation between the parties during the mediation process. Therefore, mediation plays a crucial role in assisting in the peaceful resolution of inheritance disputes and maintaining family relationships between the disputing parties.